Got your number : the greatest sports legends and the numbers they own - Greenberg, Mike, 1967-; Hembekides, Paul (2023)
"ESPN personality (Get Up and #Greeny) and New York Times bestselling author Mike Greenberg partners with mega-producer Hembo to settle once and for all which legends flat-out own which numbers. In short essays certain to provoke debate between and amongst all generations, Greeny uses his lifetime of sports knowledge to spin yarns of the legends among the legends and tell you why some have claimed their spot in the top 100 of all time." -- Amazon.com.
Keywords: Sports -- Miscellanea; Sports -- History -- Miscellanea; Athletes -- Miscellanea; Professional athletes -- Miscellanea; Women athletes -- Miscellanea; Sports writing; Essays; Trivia and miscellanea; Biographies